Human rights monitoring mechanisms of the Council of Europe - De Beco, Gauthier (Milton Park, Abingdon, Oxon : Routledge, 2012)
'The book studies the human rights monitoring mechanisms of the Council of Europe. It provides an in-depth examination of six such mechanisms: the Commissioner for Human Rights, the European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment (the CPT), the European Committee of Social Rights (the ECSR), the Advisory Committee on the Framework Convention for the Protection of National Minorities (the ACFC), the European Commission against Racism and Intolerance (ECRI) and the Committee of Experts of the European Charter for Regional or Minority Languages (the CECL). The human rights monitoring mechanisms of the Council of Europe seek to establish a permanent dialogue with governments to encourage them to better implement human rights treaties. They function principally through the use of national reports, on which basis they make recommendations, and may also visit or question states directly. The book looks at each mechanism in turn, discussing their composition, functions and working methods, as well as their relationship with other actors. It includes both a general discussion of the role of European human rights monitoring mechanisms as well as a comparative analysis of these mechanisms. The book aims to provide a clear understanding of the underlying approach of European human rights monitoring mechanisms and the challenges faced by them in terms of effectiveness. It will be useful for practitioners and students alike, especially those following courses in human rights or related fields'--Provided by publisher.
The Commissioner for Human Rights / Lauri Sivonen -- The European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment (the CPT) / Renate Kicker -- The European Committee of Social Rights (the ECSR) / Olivier De Schutter and Matthias Sant'Ana -- The Advisory Committee on the Framework Convention for the Protection of National Minorities (the ACFC) / Gauthier de Beco and Emma Lantschner -- The European Commission against Racism and Intolerance (ECRI) / Lanna Yael Hollo -- The Committee of Experts of the European Charter for Regional or Minority Languages (the CECL) / Robert Dunbar -- Conclusion. A comparative analysis of European human rights monitoring mechanisms / Gauthier de Beco.
Includes bibliographical references and index.
Keywords: Council of Europe; Human rights monitoring -- Europe; Human rights -- Europe